Bioactive Compounds in Edible Oils and Their Role in Oxidative Stress and Inflammation - Mazzocchi, Alessandra; De Cosmi, Valentina; Risé, Patrizia; Milani, Gregorio Paolo; Turolo, Stefano; Syrén, Marie-Louise; Sala, Angelo; Agostoni, Carlo (Frontiers in Physiology, 2021)
Diet and inflammatory response are recognized as strictly related, and interest in exploring the potential of edible fats and oils for health and chronic diseases is emerging worldwide. Polyunsaturated fatty acids present in fish oil, such as eicosapentaenoic acid and docosahexaenoic acid, may be partly converted into oxygenated bioactive lipids with anti-inflammatory and/or pro-resolving activities. Moreover, the co-presence of phenolic compounds and vitamins in edible oils may prevent the development of chronic diseases by their anti-inflammatory, antioxidant, neuroprotective and immunomodulatory activities. Finally, a high content in mono-unsaturated fatty acids may improve the serum lipid profile, and decrease the alterations caused by the oxidized low-density lipoproteins and free radicals. The present review aims to highlight the role of lipids and other bioactive compounds contained in edible oils on oxidative stress and inflammation, focusing on critical and controversial issues that recently emerged, and pointing to the opposing role often played by edible oils components and their oxidised metabolites